Effects of Injection Recombinant Growth Hormone Kertang Grouper (rElGH)With Different Doses To Growth Mud Crab (Scylla serrata) - Fitriyani Fitriyani; Rusliadi Rusliadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Mud crab (Scylla serrata) is commodity fisheries that have high economic value. Enlargement of mud crab requires a relatively long time and growth is not optimal. The acceleration of growth can be done by applying the Recombinant Growth Hormone to the grouper kertang (rElGH), so that the growth rate will take place more quickly. In the enlargement activity, the injection ofr is not yet known rElGH which can stimulate the growth of mud crab. This study aims to determine the dose of rElGHto produce the best growth of mud crab. The benefit of this research is to provide information about the growth of mud crab injected rElGHwith different dosages. This research was carried out in April to May 2020 for 28 days in the Center for Brackish Aquaculture Fisheries (BBPBAP) Jepara, Central Java Province. The method used in this research is the experimental method. Complete Randomized Design (CRD) one factor with 4 levels of treatment and 3 replications. The treatment stages in this study were P0 (without injection rElGH), P1 (injection of 1 μg rElGH / g Mud crab), P2 (injection of 1.5 μg rElGH / g Mud crab), and P3 ( Injecting a dose of 2 μg rElGH / g Mud crab). The results showed that the injection of rElGH in mud crab with different doses gave growth results that were not significantly different between treatments. P0 has the best results, namely an absolute weight 9,04±0,31ag, a specific growth rate 0,41±0,01a%, carapace width growth 0,35±0,02acm, feed conversion 6,87±0,22aand a survival rate 83,33±28,86a%. Keywords:Injections, mud crab, rElGH and growth